Flow visualization of heavy oil in a packed bed using real-time neutron radiography. (16th March 2019) - Shoji, Eita; Yamagiwa, Koshiro; Kubo, Masaki; Tsukada, Takao; Takami, Seiichi; Sugimoto, Katsumi; Ito, Daisuke; Saito, Yasushi; Teratani, Shogo
Highlights: Heavy oil flows in a packed bed simulating a trickle bed reactor were visualized using real-time neutron radiography. Effects of temperature, N2 gas flow rate and size of packed particles on the flow behaviors were investigated. Head velocities and flowing areas of the heavy oil flows were measured. Capability of neutron radiography to study heavy oil flows in a metallic reactor was presented. Abstract: Neutron radiography can visualize heavy oil flows in metallic reactors used to upgrade heavy oils. Thus, we visualized heavy oil flows in a packed bed using real-time neutron radiography to support its capability and to offer basic experimental data necessary for verification and validation of numerical simulations. Atmospheric residue was used as the heavy oil sample and heavy oil and N2 gas were concurrently supplied into a packed bed from above a reactor simulating a trickle bed reactor. Reactor temperatures were set at either 100°C or 250°C to change heavy oil viscosity. The heavy oil flow rate was kept constant at 2.5 mL/min and the N2 gas flow rate was set at either 1 L/min or 3 L/min at 25°C. A series of neutron radiography experiments was conducted at the B-4 neutron imaging facility in the Kyoto University Research Reactor (KUR) with a thermal neutron flux of 5 × 10 7  n/cm 2 ⋅s. We performed image processing for the neutron radiographs to calculate neutron beam attenuation and clarify flow behavior. Visualization results show differences in flow behavior depending on operating factors. Temperature had a particularly substantial effect on flow behavior because heavy oil viscosity depends strongly on temperature. The flows also showed different behaviors for 1 mm and 3 mm packed particle sizes because the void ratios in the packed bed, which were preliminarily observed by X-ray computational tomography (CT), change with particle size. Channeling flow was observed with 3 mm particles and a temperature of 250°C. Furthermore, this work suggests that neutron radiography can be used to investigate heavy oil flows in metallic reactors.